PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KARTU PANGGILAN TERHADAP MOTIVASI BELAJAR PKN SISWA KELAS VII SMP NEGERI 34 PEKANBARU - Syahfitri, Isti; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research entitled "The Effect of Using Call Card Learning Model on PKn Learning Motivation Grade VII Students of Pekanbaru State Junior High School 34". Against the background of the low PKn learning motivation with symptoms such as still there are students who are not diligent in doing the task, are not active and do not work independently. The formulation of the problem in this study is "Is there any influence on the use of the Call Card learning model on PKn learning motivation in class VII Pekanbaru 34 SMP Negeri". The purpose of this study is to find out whether there is an effect of the use of the Call Card learning model on PKn learning motivation of Grade VII students of Pekanbaru State Junior High School 34. The population of this study was all students of class VII Pekanbaru 34 Middle School. This research was conducted in March-April 2019. Techniques for collecting data by observation, questionnaire, and documentation. Data analysis techniques using Quantitative Descriptive methods. In conclusion, the average learning motivation of the experimental class increased from 17.47 to 21.93. While the control class from 18.25 to 21.11. Based on the analysis of the "t" difference test, the two classes show t count> t table (63.92> 1.66) which means there is an influence and with the contribution of the experimental class gain of 0.40 in the "average" category. The hypothesis proposed is that "There is the influence of the use of call card learning models on PKn learning motivation of seventh grade students of Pekanbaru Public Middle School 34", AcceptedKey Words: Call Card, Motivation Study